PENGARUH PE`MAKAIAN MASKER TEMULAWAK TERHADAP PERAWATAN KULIT WAJAH BERJERAWAT - Putri Yulianti, Nel Ayu; Rostamailis, Rostamailis; Rahmiati, Rahmiati (Journal of Home Economics and Tourism, 2014)
This study aims to analyze the effect of the use curcuma mask for skin care facial acne were assessed in terms of color, shape, volume, and number of the acne. This study has a different treatment such as; control group, the first experimental group and the second experimental group. This type of research is a quasi-experimental study with nonequivalent control group design and the sampling technique used was purposive sampling were carried out in volunteers. The samples in this study were nine students aged 17-25 years old with type inflammatory acne. The analysis of the data is using a Varian analytical techniques and Duncan test. The results showed that the change in color, shape, volume, and number of acne in the control group didn’t show the change for the better on every indicator. In contrast, the first experimental group with frequency of use of the curcuma mask once in three days showed significant influence in every indicator. Meanwhile, in the second experiment with the frequency of use once a week showed significant results in each indicator. The use of curcuma mask regularly with a frequency of 1 x 3 days and 1 x a week has provide significant result towards a better.Keywords: Curcuma Mask, Treatment, Acne Prone Skin